Fault Diagnosis for Gearbox Based on Improved Empirical Mode Decomposition - Ling Zhao; Darong Huang; Yi Qin (Shock and Vibration)
The application of the improved empirical mode decomposition (EMD) theory in gearbox fault diagnosis has been studied in this paper, and the transient features of gearbox vibration signals are shown. Based on using EMD, an improved algorithm of orthogonal empirical mode decomposition (OEMD) is put forward and is applied to extract the fault feature. Finally, fault diagnosis application in a gearbox is used as an example to prove the feasibility of the proposed method.